How do you get that lower equation from the upper one?
Follow Math Help Forum on Facebook and Google+
Hi Take the natural log of the upper equation $\displaystyle \ln \left(e^{-kt}\right) = \ln \frac12$ ln being the inverse function of exp, $\displaystyle \ln(e^x) = x$ The equation becomes $\displaystyle -kt = \ln \frac12$
thanks.
Also $\displaystyle \ln \left(\frac{1}{2}\right) = \ln (2^{-1}) = -\ln(2)$ So $\displaystyle kt = \ln(2)$ which is a more usual form in exponential decay
View Tag Cloud